Educational technologies for children about parasitic diseases: an integrative review - Silva, Jaira dos Santos; Freitas, Daniela Reis Joaquim de (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Parasitic diseases have been causing serious public health problems around the world, especially in developing countries, with children being considered a more vulnerable group. This study aimed to identify educational technologies developed for or aimed at children about parasitic diseases in the scientific literature. Outlining: This is an integrative review, carried out in the following databases: MEDLINE, via PubMed; Embase; Web of Science; SCOPUS (Elsevier); LILACS and CINAHL. The population, interest, context strategy was used, combined with controlled and uncontrolled descriptors and the Boolean operators AND and OR. The analysis of the studies occurred in a descriptive way. Two categories emerged: digital educational technologies developed for or aimed at children about parasitic diseases and non-digital educational technologies developed for or aimed at children about parasitic diseases. Results: Eleven studies were included. Digital technologies were identified, such as cartoons, videos, and PowerPoint presentations, as well as non digital technologies, such as comic books, leaflets, board games and printed booklets. Educational technologies developed in school environments and/or in the community were found. The parasitic diseases covered were intestinal ones, the visceral leishmaniasis, malaria, Chagas disease, lymphatic filariasis and schistosomiasis mansoni. Implications: Digital and non-digital educational technologies have proven to be motivational, attractive, and complementary technological resources that contribute to children’s active learning.